History Page: Leaders in MSK Radiology - Kainberger, Franz; Hahn, Daniela (Seminars in Musculoskeletal Radiology, 2021)
Robert Kienböck (1871–1953) may be regarded as one of the first musculoskeletal radiologists who began his clinical and scientific work 2 years after the discovery of X-rays. He lent his name to Kienböck's disease, a traumatic malacia and osteonecrosis of the lunate, and to several other eponyms of diseases, devices, and parameters in radiology and radiation oncology. With his meticulous analysis of radiographic images of the highest quality, he anticipated many theories that were proposed in later decades.
Keywords: history; avascular necrosis of the lunate; Kienböck's disease